Digital Media for Youth Awareness on Corruption and Human Rights - Kirana Putri, Sasi Azhari; Kunanti, Nadia; Putri, Syarifah Sukma (Jurnal Multidisiplin Indonesia, 2026)
Corruption and human rights violations remain significant global challenges that undermine democratic governance, public trust, and social justice. Despite their structural impact, these issues are often perceived by young people as distant political problems rather than everyday realities. This study aims to examine how digital educational media can enhance youth awareness of corruption and human rights violations. A qualitative descriptive design was employed using purposive sampling. Ten law students who had completed courses related to constitutional law and human rights participated in semi-structured interviews. The data were analyzed using thematic analysis to identify key themes related to everyday corruption and rights violations. The findings informed the development of a short educational video distributed through TikTok and Instagram. Audience comments were observed and analyzed descriptively to identify recurring response patterns over a two-week period, assessing awareness, emotional engagement, and expressions of responsibility. The results reveal three primary outcomes: increased recognition of everyday corrupt practices, heightened emotional and moral engagement, and emerging civic responsibility among viewers. These findings align with recent digital civic engagement theories suggesting that online participation often begins with awareness and expressive reflection before evolving into broader civic action. This study highlights the potential of short-form digital media as a complementary tool for civic education and recommends integrating digital campaigns with institutional collaboration and mixed-method evaluation to ensure sustainable impact.